Cardiovascular consequences of aircraft noise exposure - Justyna Ba̧czalska; Wiktoria Wojciechowska; Marta Rojek; Omar Hahad; Andreas Daiber; Thomas Münzel; Marek Rajzer (Frontiers Media S.A., 2022)
The results from epidemiological studies suggest that environmental noise including aircraft, railway, road traffic, wind turbine, and leisure-related noise is a growing public health concern. According to the WHO, at least 100 million people in the European Union are affected by traffic noise levels above the WHO-recommended thresholds. Environmental noise can adversely affect physical and mental health, as well as wellbeing. Chronic low-level noise exposure typical for most environmental sources is associated with psychophysiological stress causing non-auditory or indirect noise effects leading ultimately to cardiovascular diseases. Among all environmental noise sources, aircraft noise is considered the most annoying, and its leading mechanism of action is autonomic system activation such as increases in heart rate and blood pressure. Previously, we observed that long-term exposure to aircraft noise was associated with increased diastolic blood pressure, arterial stiffness (as assessed by pulse wave velocity), and impaired left ventricular diastolic function. All mentioned above effects are early, subclinical, and potentially reversible changes which preceded late noise effects in the cardiovascular system, that is, established cardiovascular diseases such as myocardial infarction, stroke, and heart failure. However, even a short-term reduction in aircraft noise exposure as observed during the COVID-19 lockdown may reverse these negative effects on arterial stiffness and blood pressure and may decrease the prevalence of insomnia. In this review, we aimed to critically discuss our obtained results considering recent studies on the influence of aircraft noise (and other traffic noises) on cardiovascular diseases in the context of the WHO Environmental Noise Guidelines for the European Region.